THE SIGNIFICANT EFFECT OF TASK-BASED GROUP ACTIVITIES ON STUDENTS' COLLABORATIVE BEHAVIOR IN READING CLASS OF EIGHTH GRADE AT SMP HKBP PADANG BULAN MEDAN - Helen Patricia Sitanggang; Yessy Octavianna; Carolina Pakpahan (Sean Institute, 2023)
This study was intended to determine the significant effect of Task-Based Group activities on students' collaborative behavior in reading class. The objectives of this study was to find out whether there is a significant effect of Task-Based Group activities on students’ collaborative behavior in reading class of Eighth Grade at SMP HKBP Padang Bulan Medan, used a quantitative experimental research design. The population of this study were eighth grade students of SMP HKBP Padang Bulan Medan, grades VIIIA and VIIIB. The number of students is 40 students as a sample for each class consisting of 20 students. Students were divided into two groups, namely the experimental group and the control group. The experimental group was given treatment (Task-Based Group Activities), while the control group was taught conventional methods. The instrument used to collect data is a multiple choice test. Data were analyzed using the t-test formula. The results of the analysis show that to be served is higher than t-table (5.81 > 1.27) at a significance level of 0.05 with degrees of freedom (df) 38. This means that the use of Task-Based Group Activities in the teaching and learning process has succeeded in influencing student learning scores, especially in class reading descriptive text.